MODELLING AND OPTIMIZATION OF RECIRCULATION RATIO AND INTERMITTENT AERATION FOR ORGANIC REMOVAL IN MODIFIED SEPTIC TANK AS A WASTEWATER TREATMENT SYSTEM FOR OFFICE BUILDING - Fadwah Zakiyah, Siti
The domestic wastewater of office building has spesific characteristics, containing high levels concentration of organic and nutrient matter. Moreover, the various of domestic wastewater is due to activities, facilities, and the number of people in the building. The spesific characteristic wastewater from office building are organic matter 106 until 432 mg COD/L, nutrient 41 until 114 mg N/L, and 0.99 until 8.21 mg P/L. Therefore, in order to improve the quality of treated wastewater, it is necessary to modify the convensional septic tank (CST). This study used secondary data from previous studies using the lab-scale of modified septic tank (MST) with hydroulic retention time (HRT) 36 hours and organic loading rate (OLR) 0.17 kgCOD/m3.day. The effect of variables was studied on the variation of recirculation ratio (RR) 2, 3, and 4 for kaldnes media, and RR 3/2, 3, and 5 for sponge media, intermittent aeration (IA) 6, 12, and 24 hours for both types of media. The lab-scale of the MST consists of four compartements: anoxic 1, anoxic 2, MBBR, and sedimentation compartments. The objective of this study is to know the optimum condition of recirculation ratio and intermittent aeration for COD and BOD5 removal using Design Expert Software (Version 7.0) with the desirability fuction approach. The response surface methodology showed that quadratic model has been chosen to response the efficiency of COD and BOD5 for both kaldnes and sponge media. The optimization process has been conducted from the mathematical model obtained and statistical analysis with a confidence level of 95%. The optimum conditions were obtained for kaldnes media at RR 3.4 and IA 6 hours for COD removal efficiency of 87.8513% and BOD5 removal efficiency of 92.7184%. Sponge media has lower effectiveness than kaldnes, namely at the RR level of 3.73 and IA 6 hours for COD removal efficiency of 67.6617% and BOD5 removal efficiency of 64.7643%. In this optimum condition, the concentrations of COD and BOD5 have met the quality standards for domestic wastewater based on PerMenLHK (Regulation of the Minister of Environment and Forestry) No. 68 of 2016.